SPACE TIME MAPPING OF ENVIRONMENTAL NOISE IN THE URBAN AREA OF RIOBAMBA (ECUADOR) (Lex localis - Journal of Local Self-Government, 2025)
The objective of this research was to generate a spatio-temporal mapping of environmental noise in the urban area of the city of Riobamba (Ecuador), through the use of geographic information technologies focused on spatial analysis and geostatistical methods, as well as acoustic evaluation methods with compatibility based on the ISO 12913-2:2018 Acoustics-Soundscape Part 2 standard.  generating indicators that allow the management of the territory considering territorial environmental criteria and especially with the factor called noise pollution, constituting a contribution to the development of policies aimed at environmental sustainability in urbanization processes. The analytical results revealed that the study area suffers from noise pollution, where a high percentage of the population is exposed to unacceptable noise environments, indicating that strategies to improve noise control are urgent.